2010
DOI: 10.1007/s12651-010-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-wage careers: Are there dead-end firms and dead-end jobs?

Abstract: Using representative linked employer-employee data of the German Federal Employment Agency, this paper shows that just one out of seven full-time employees who earned low wages (i.e., less than two-thirds of the median wage) in 1998/99 was able to earn wages above the lowwage threshold in 2003. Bivariate probit estimations with endogenous selection indicate that upward wage mobility is higher for younger and better qualified low-wage earners, whereas women are substantially less successful. We show that the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 15 publications
(20 reference statements)
2
43
0
1
Order By: Relevance
“…The probability of being low-paid tends to decrease with a worker's qualification level (Figure 2), but it is notable that (in some countries) significant shares of skilled workers are also engaged in low-wage employment. These findings are confirmed by other studies for the EU [5] and for a number of countries like Denmark, the Netherlands, Italy, and Spain [7]; Germany [8]; the UK [9]; and Australia [3].…”
Section: Who Are the Low-paid?supporting
confidence: 86%
See 1 more Smart Citation
“…The probability of being low-paid tends to decrease with a worker's qualification level (Figure 2), but it is notable that (in some countries) significant shares of skilled workers are also engaged in low-wage employment. These findings are confirmed by other studies for the EU [5] and for a number of countries like Denmark, the Netherlands, Italy, and Spain [7]; Germany [8]; the UK [9]; and Australia [3].…”
Section: Who Are the Low-paid?supporting
confidence: 86%
“…Concerning individual worker characteristics, not only is low-wage employment more prevalent among female and low-skilled workers, but the chances that these groups are able to escape from low-paid jobs are also generally more limited [6], [7], [8]. In contrast, younger workers at the beginning of their careers exhibit a higher probability of moving up the wage ladder than older workers [6], [8].…”
Section: Upward Mobility Of Low-paid Workersmentioning
confidence: 99%
“…However, for a significant number of employees such as women, the less educated and the aged, the low wage situation tends to be persistent and lasting once in it. Similar results were obtained in Portugal by Vieira (2005) and Germany by Mosthaf et al (2011). Deding (2002) concluded that women are at a greater risk than men of remaining low-wage employees in Denmark and the USA.…”
Section: Literature Reviewsupporting
confidence: 68%
“…According to Mosthaf et al (2011), in their study for Germany, companies with an elevated proportion of low wage workers offer them few opportunities to get out of this situation. The same applies to those found in occupations with a high percentage of low income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mobility from low pay to higher wages is more frequent with younger and better skilled workers as well as male workers in general, in particular if they can leave (i) firms with large segments of low paid jobs and (ii) unskilled service occupations (Mosthaf et al 2011).…”
Section: Fig 3: Working-age Population By Employment Status 1992-2012mentioning
confidence: 99%